2010
DOI: 10.4238/vol9-1gmr678
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of Byrsonima verbascifolia (Malpighiaceae) against damage induced by doxorubicin in somatic cells of Drosophila melanogaster

Abstract: ABSTRACT. Byrsonima verbascifolia, popularly known in Brazil as murici, is a medicinal plant widely used in the treatment of bacterial and viral infections, Chagas's disease, diarrhea, bronchitis, cough and fever, as well as for protection of the intestinal mucosa. Since chemotherapy and radiotherapy, broadly employed in the treatment of cancer, can have undesirable side effects, such as inducing DNA damage in normal cells, it would be useful to investigate compounds that inhibit or reduce these effects. A lyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
2
10
0
7
Order By: Relevance
“…In high bioactivation (HB) crossing, 80 female ORR lineage were crossed with 40 mwh males. In both crosses the following offspring was obtained: marked trans-heterozygous (MH) with genetic constitution mwh +/+ flr 3 , which can be easily identified by the smooth wings (Ribeiro et al, 2003(Ribeiro et al, , 2009Valadares, 2007;Mendanha et al, 2010).…”
Section: Melanogaster Strains and Crossesmentioning
confidence: 99%
See 1 more Smart Citation
“…In high bioactivation (HB) crossing, 80 female ORR lineage were crossed with 40 mwh males. In both crosses the following offspring was obtained: marked trans-heterozygous (MH) with genetic constitution mwh +/+ flr 3 , which can be easily identified by the smooth wings (Ribeiro et al, 2003(Ribeiro et al, , 2009Valadares, 2007;Mendanha et al, 2010).…”
Section: Melanogaster Strains and Crossesmentioning
confidence: 99%
“…The test is based on the identification of mutant phenotypes that are originated due to the occurrence of DNA damage, caused by the loss of larval heterozygous cells (Fonseca and Pereira, 2004;Ribeiro et al, 2003Ribeiro et al, , 2009Mendanha et al, 2010;Abreu et al, 2011;Alte et al, 2012). The test makes use of three D. melanogaster different strains: (i) multiple wing hairs (mwh); (ii) flare-3 (flr 3 ); and (iii) ORR/ORR.…”
Section: Introductionmentioning
confidence: 99%
“…A. Juss (Malpighiaceae) é popularmente conhecida como "murici" (Morais et al, 2013), "murici-cascudo", "mirici", "douradinha-falsa","muricizinho", "orelha-de-burro", "orelha-de-veado", "semaneira", "baga-de-tucano" (Mendanha et al, 2010). Possui hábito subarbustivo (Barbosa et al, 2005) e folhas grandes e rígidas (Andrade et al, 1995), com pêlos em ambas faces (Andrade et al, 1995;Andrade et al, 1999).…”
Section: Descrição Botânicaunclassified
“…Silva (1998) These results are in accordance with those observed in the present study, which also showed the modulatory effect of D. furfuracea infusion on the damage caused by urethane. Mendanha et al (2010) observed the antigenotoxic activity of the aqueous extract of Byrsonima verbascifolia using the SMART/wing test/wing. This medicinal plant has chemicals that are also present in D. furfuracea, such as flavonoids and terpenes, corroborating the results found in this study.…”
Section: Ls Coelho Et Almentioning
confidence: 99%